2002
DOI: 10.1021/cm010498j
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Interaction Characteristics of Organically Modified Montmorillonite Nanocomposite with Miscible Polymer Blend of Poly(Ethylene Oxide) and Poly(Methyl Methacrylate)

Abstract: The intercalation of organically modified montmorillonite (OMMT) in the polymer blend of poly(ethylene oxide) (PEO) and poly(methyl methacrylate) (PMMA) has been demonstrated using dichloromethane as the cosolvent at room temperature. X-ray diffraction has been used to confirm the formation of nanoscale polymers-OMMT hybrids and the localization of the polymers between the organosilicate layers. The silicate nanocomposites have higher tensile modulus and elongation at break than the polymer matrix, revealing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(52 citation statements)
references
References 35 publications
1
48
1
Order By: Relevance
“…Several routes were developed to achieve a high degree of dispersion of the clay nanoplatelets which are described in details in a recent review of literature realized by Alexandre and Dubois [6]: (i) in situ polymerization of monomers which were initially intercalated between silicate layers [7][8][9][10], (ii) melt intercalation and further exfoliation for thermoplastic polymers [11][12][13], and (iii) combination with a polymer solution [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Several routes were developed to achieve a high degree of dispersion of the clay nanoplatelets which are described in details in a recent review of literature realized by Alexandre and Dubois [6]: (i) in situ polymerization of monomers which were initially intercalated between silicate layers [7][8][9][10], (ii) melt intercalation and further exfoliation for thermoplastic polymers [11][12][13], and (iii) combination with a polymer solution [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In miscible systems, such as poly(methyl methacrylate) ( PMMA )/ poly(ethylene oxide) ( PEO ) [19,20] , the morphological analysis can be carried out as in a general polymeric matrix. However, in immiscible systems, such as poly(propylene) ( PP )/ poly(styrene) ( PS ), both XRD patterns and TEM observations have shown that the silicate layers were either intercalated or exfoliated, depending on their interactions with the polymer pair, and were located at the interface between the two polymers [21] .…”
Section: Morphology Of Compositesmentioning
confidence: 99%
“…Polyethylene oxide attains a high degree of crystallinity, approximately 60 %, at room temperature. Polymer blends display a practical and efficient way to fulfill novel requirements for material properties and applications [9,10]. The addition of salt to the polymer provides mobile ions and the polymer host chains play a critical role in ionic transport process of the polymer electrolytes.…”
Section: Introductionmentioning
confidence: 99%